“We agreed to write (live)”: Survivor-analysts with students from a public school in Fortaleza/CE: Analisadores-escreviventes com estudantes de uma escola pública de Fortaleza/CE (TEL Tempo, Espaço e Linguagem, 2024)
The article aims to discuss the contributions of Conceição Evaristo's Escrevivência to a research-intervention on gender WITH students from a public school on the outskirts of Fortaleza, Ceará. We discuss analyzers triggered by escrevivência, such as: Rescue of speech, Denunciation, Epistemic disobedience, Writing of us and Registration. In this way, escrevivência provided a possible way for young people to tell their stories in opposition to coloniality.